Tranexamic Acid Inhibits Fibrinolysis, Shortens the Bleeding Time and Improves Platelet Function in Patients with Chronic Renal Failure - Mezzano, Diego; Panes, Olga; Muñoz, Blanca; Pais, Edgar; Tagle, Rodrigo; González, Fernando; Mezzano, Sergio; Barriga, Francisco; Pereira, Jaime (Thrombosis and Haemostasis, 1999)
Background: A defect in platelet function is the main determinant of the prolonged bleeding time in chronic renal failure (CRF). We previously reported a significant correlation between platelet abnormalities and elevated plasma markers of plasmin and thrombin generation. Our aim was to explore the effect of inhibiting both plasmin action with tranexamic acid (TA) and thrombin production with low molecular weight heparin (LMWH), on the bleeding time (BT) and platelet function in patients with CRF. Methods: 37 patients with CRF (mean creatinine 8.6 ± 4.4 mg/dl) under conservative treatment, with prolonged BT, entered this study and received TA during 6 days, with (n = 24) and without LMWH (n = 13). BT, platelet aggregation/secretion, platelet granule contents, von Willebrand factor and parameters of coagulation and fibrinolysis were recorded before and at the end of treatment. Results: The BT was shortened in 26/37 (67%) patients. This effect was associated with significant improvement of platelet aggregation and secretion, with decrease to a normal range of fibrin/fibrinogen degradation products, mild increase in plasmin-antiplasmin complexes and pronounced reduction of circulating plasminogen. No differences were seen among patients with or without LMWH. No serious side effects or complications were observed. Interpretation: These findings indicate that the activation of fibrinolysis plays a significant role in the defect of primary hemostasis in patients with CRF. Inhibition of plasmin activity with TA shortens the BT and improves platelet function in the majority of patients with severe disease.